Income taxes, public fiscal policy and economic growth - Tomasz Wołowiec; Tomasz Skica; Galya Gercheva (e-Finanse: Financial Internet Quarterly, 2014)
The main goal of this article is to find the relationship between public fiscal policy and economic growth. The article consist of a few parts. The first is an introduction, which creates the background for the analysis in the following sections. It shows the main point of view on public fiscal policy especially in the case of personal income tax and creates a framework for the analysis of the relationship between taxation and economic growth. The second part focuses on the relations between central government decisions on taxation and its influence on savings, investments and economic growth. In this part we will find selected analyses of the impact of taxes on economic growth based on the examples of OECD countries. Finally, the last part of the work is a study on fiscal level and tax system structures and economic growth. In this part the authors checks two points of view on taxation. The first is that a low level tax burden is conducive to economic growth, and the second emphasizes negative consequences of decreasing budget tax revenues. The article shows both theoretical and empirical points of view on taxation and influence of government taxation decisions on the economy.
Keywords: H21; H24; H30; E62; F43; 330; personal income tax; corporate income tax; budgetary system; fiscal policy; economic growth